Critical factors to predict efficacy of orthokeratology in inhibiting axial elongation in myopic children - Yuanqi Deng; Xuewei Li; Mingwei Zhao; Yan Li; Kai Wang (BMC Ophthalmology)
Abstract Background The efficacy of orthokeratology (Ortho-K) in controlling myopia is influenced by many complex factors, which makes predicting the effect of myopia control a complicated task. This study aimed to analyze the relevant factors that can predict the axial length elongation (ALE) in patients wearing Ortho-K, including baseline ocular parameters, genetic factors and lifestyle habits. Methods In this retrospective study, 542 eyes from 300 myopic children wearing Ortho-K were reviewed from the Optometry Centre of Peking University People’s Hospital from January 2022 to December 2023. Baseline characteristics such as age, gender, spherical equivalent refraction (SER), horizontal visible iris diameter (HVID), mean keratometry value (mean K), corneal astigmatism, corneal eccentricity (E-value), anterior chamber depth (ACD), central corneal thickness (CCT), pupil diameter (PD), treatment zone area (TZA) and treatment zone decentration distance were measured. Additionally, parental factors and lifestyle habits, including parental myopia status, continuous near-work time, weight change, height change, age of diagnosis of myopia, eating sweets, regular follow-ups, online-class, interest class, outdoor activity and reading and writing posture were collected via questionnaires. Linear mixed effect model was constructed to identify factors associated with ALE. Results Linear mixed effect model revealed that patients had a higher ALE who started wearing Ortho-k lenses at a younger age (P < 0.001), had less myopia (P < 0.001), high-myopia in both parents (P = 0.018). Conversely, patients had slower ALE with a larger decentration distance of the treatment zone (P = 0.002) and regular follow-ups (P = 0.001). Conclusions Age, SER and parental high myopia are critical factors to predict efficacy of orthokeratology in inhibiting axial elongation in myopic children. Orthokeratology lens decentration and regular follow-ups have a positive impact on myopia control. The decentration can be considered preserved when there is no obvious visual interference or complications.